INNOVATION ADOPTION PROCESS IN CREATING CUSTOMER VALUE PT.PLN - Hadi Ahmad Sukardi; Ratih Nurriyati; Puspo Dewi Dirgantari (LPPM Universitas Sangga Buana, 2023)
The consumer adoption process is a process in which consumers assimilate information, use it, and verify what has been done. The many innovations implemented in the PT. PLN company will certainly have an impact that has value in front of customers. In carrying out the process of consumer adoption of schemes or innovations imposed by PT. PLN. With the innovation carried out by PLN, namely the use of the PLN mobile application, will there be a problem between the previous habit becoming a new habit, of course PLN customers must get used to adapting to this habit. This research certainly wants knowledge between the researchers' assumptions namely product quality, product design and product benefits in the adoption process of the PLN influencing customer assessment. Correlational Research Methods where researchers change qualitative data into quantitative data by using primary data and using the slovin method as a sample data selection. The analysis technique using structural equation modeling rather obtains accurate hypothesis results and uses validity and reliability tests using variance extract and construct reliability. As well as this research confirms the model suitability test by using the Goodness of fit test and finally the researcher gets the results of the regression weight for the results of determining the hypothesis. The results obtained by the researchers in this study were that product quality had a significant and positive effect on customer ratings, while product design had no significant relationship with customer ratings and product benefits/usages also had no significant relationship at all with PLN product ratings.